2015
DOI: 10.1155/2015/845870
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Adenocarcinoma in a Horse with Metastasis to Lung, Liver, and Bone and Review of Metastasis in Nine Horses with Sinonasal Tumors

Abstract: Sinonasal neoplasia metastasizing to distant organs is rare in horses. This case report describes the clinical and imaging findings of a horse with sinonasal neoplasia, which had metastasized to the lung, liver, and humerus. Additionally, the prevalence of sinonasal neoplasia and their incidence of distant metastasis among horses that presented to the Oregon State University Veterinary Teaching Hospital (OSU-VTH) were estimated. Of 5,558 equine patients who presented to the OSU-VTH in the last nine years, 1.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Direct visualization of the neoplasm was possible in 13 out of 20 cases reported by Dixon et al [3]; the exam is also useful when there are deformities in the upper airways [23]. Cases of adenocarcinoma often present as lobulated masses in the ethmoid region, in a typical location of ethmoid hematoma [8,11], as was initially suspected in case 2. Reports of ossifying fibroma, as observed in the present case, present with historical frequency of noise and difficulty breathing [15,20].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Direct visualization of the neoplasm was possible in 13 out of 20 cases reported by Dixon et al [3]; the exam is also useful when there are deformities in the upper airways [23]. Cases of adenocarcinoma often present as lobulated masses in the ethmoid region, in a typical location of ethmoid hematoma [8,11], as was initially suspected in case 2. Reports of ossifying fibroma, as observed in the present case, present with historical frequency of noise and difficulty breathing [15,20].…”
Section: Discussionmentioning
confidence: 96%
“…All cases presented with purulent nasal discharge, being bilateral in 3, with a longer evolution time. There are few reports of epistaxis [8], which was initially observed in case 2, where it is suggested to be due to the involvement of the ethmoid. Increases in facial volume are common, usually firm, with no pain on palpation and greater when compared to sinusitis of dental origin [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the lesion caused by the tumor mass in expansion caused chronic sinusitis, with purulent and fetid nasal discharge at the affected site. In a retrospective study in which 5,558 horses were evaluated, sinonasal diseases were identified in 1.4% of the cases, and from these, 0.14% were nasal cavity tumors, all of them showing nasal discharge [8].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the prevalence of neoplasia in horses is rather rare, but the head is a more commonly affected location in the horse ( 56 ). Differentiating various soft tissue tumor types using CT is often challenging as they share similar imaging features; however, CT provides useful information in staging the lesion by evaluating the origin, extent and vascularity of these masses ( 91 ), facilitating planning for biopsy or surgical resection. CT examination of soft tissue masses of the head should include intravenous iodinated contrast medium administration unless there is a known contraindication such as allergy.…”
Section: Imaging Specific Disorders Of the Equine Headmentioning
confidence: 99%